Environmental stressors in biology and medicine - Valacchi, Giuseppe (Annals of the New York Academy of Sciences, 2012)
"As research on the etiology and pathophysiology of disease states continues to expand, more attention has been paid to the contribution of exogenous factors, such as nutrition and toxin exposure. Convening at the Second International Conference on Environmental Stressors in Biology and Medicine, October 5-7, 2011 in Siena, Italy, international experts presented work examining the impact of a range of environmental stressors impinging on the biological basis of disease development. Papers based on these proceedings and assembled in this volume include short reviews on the basic mechanisms of and diseases related to everyday environmental stressors, such as exposure to cigarette smoke and air pollutants; the development and identification of pharmaceuticals and nutraceuticals, which may protect against or ameliorate cellular stress; and the role of environmentally induced stress in a number of conditions, including cancer, Alzheimer's disease, and pulmonary disease"--Society webpage.